DETERMINATION OF CHARACTERISTICS OF THROTTLING DEVICE FOR PNEUMATIC SPRING - Reidemeister, O. H.; Laguza, A. V. (Science and Transport Progress, 2021)
Purpose. This paper focuses on determination of the dependence of the working medium flow on the capacity of the throttling device, its geometric features and the pressure difference in the pneumatic spring cylinder and in the auxiliary reservoir. Methodology. Calculation of the dependence of the working medium and pressure drop is performed in two ways: 1) by numerical simulation of a stationary gas flow through a throttling element; 2) its analytical calculation expression using empirical relationships (control calculation to evaluate the reliability of numerical simulation results). For the calculation, three models of throttling devices were chosen. Dependence of the flow rate of the working medium on the capacity of the throttling device and its geometric features was determined based on the approximation of the dependency graphs of the pressure drop against the mass flow rate of the working medium. Findings. We obtained graphical dependencies between the pressure drop and the mass flow rate of the working medium from the two calculation options. Based on the results of calculations performed with the help of a software package with visualization of the results, we calculated a proportionality coefficient that describes the dependence of the working medium flow on the throttling device capacity and its geometric features for each of the throttling elements considered, with three degrees of closure. The air flow values, obtained by numerical simulation, are greater than the flow rates obtained from semi-empirical formulas. At the same time, they are in good qualitative agreement, and the quantitative difference averages 25%, which can be regarded as confirmation of the reliability of the nu-merical model. Based on the calculation results, we plotted the proportionality coefficient graphs against the degree of closure of the throttling device. Originality. The work allows determining the degree of influence of the frictio-nal component on the variation of the pressure difference in the pneumatic cylinder and the auxiliary reservoir of the pneumatic suspension system. Also, the work proposes a method to determine the dependence of the working medium on the capacity of the throttling device and its geometric features. Practical value. The ability to predict the operating parameters of the pneumatic system depending on the pneumatic resistance of the throttling device will improve the car running characteristics, increase the comfort of passenger transport, and also reduce the wear of the rolling stock and track gauge due to vehicle-track interaction.